OPTIMIZATION OF TOURISM DEVELOPMENT AT SEGARA KIDUL NUSA PENIDA TEMPLE AS AN EFFORT TO PROMOTE AND STRENGTHEN THE COMMUNITY'S ECONOMY: OPTIMALISASI PENGEMBANGAN WISATA PURA SEGARA KIDUL NUSA PENIDA SEBAGAI UPAYA PROMOSI DAN PENGUATAN EKONOMI MASYARAKAT - Ari Sudiartini, Ni Wayan; Giri Santika, I Putu (Universitas Nahdlatul Ulama Sidoarjo, 2025)
Segara Kidul Temple in Nusa Penida is a religious tourism destination with significant historical and spiritual value, offering great potential to support the local economy. However, the development of tourism in this area still faces several challenges, such as limited infrastructure, ineffective promotional strategies, and low community participation in tourism management. This study aims to analyze optimization strategies for developing Segara Kidul Temple tourism as an effort to promote the destination and strengthen the local economy. This research employs a descriptive qualitative approach with data collection methods including interviews, observations, and literature studies, while also utilizing SWOT analysis to evaluate internal and external factors affecting tourism development. The findings indicate that improving accessibility, optimizing digital marketing strategies, and empowering the local economy through culturally based businesses are key strategies to enhance tourism appeal and community welfare. Furthermore, the implementation of sustainable tourism principles is essential to maintain a balance between economic, social, and environmental aspects in managing Segara Kidul Temple tourism. With the right strategies, tourism development in this area can provide long-term benefits to the community and enhance Nusa Penida’s reputation as a cultural and religious tourism destination.